A dél-dunántúli régió környezeti állapota a gazdaságfejlesztési stratégia egyik eleme - Fodor, István (Tér és Társadalom, 1994)
The modemisation efforts expressed on the basic principles of the classic economics have been ineffective so far, or have resulted in an unproportionately weak effect compared to the costs in environmental protection. It seems that a long term economic development strategy has got chances of breaking through this dilemma only if the economic thinking comprehends that the world economy is only a sub-system of the global ecological system, and this is considered at national economic, regional and local self governmental levels. This makes the completion and functioning of new ecoeconomic models necessary at regional and self governmental levels. The reason for this is the fact that these are the social, economic and natural spatial dimensions that are the most mobile and can react in the most effective ways to the challenges of the deepening environmental crisis. However slight the chance for that is for the time being, there can hardly be any other way out towards sustainable development. The author analyses the state of the environment of Southern Transdanubia, as an important element of the economic development strategy of the region, in this spirit. With the exception of some industrialised regions of Southern Transdanubia, it is just the belatedness, or the lack of the industrial development that spared the environment of a large part of the region from serious ecological degradation. Still Southern Transdanubia is not free from environmental conflicts, either. Already there are several local issues that cannot be solved from local resources, alone. These are discussed in detail in the study. In order to deal with the most significant environmental problems, it would be necessary to create regional resources, but if the region lacks them, even the solution of region conflicts must be financed from the national level (e. g. the treatment and neutralising of dangerous waste products generated or stored in the region). The want of these can be a serious hindrance to the economic development strategies.